2019
DOI: 10.1002/slct.201803838
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Binding Mechanism of a Pyrazino[1,2‐a]indole Derivative with Calf Thymus DNA

Abstract: This work was focused on understanding the interaction mechanism of pyrazino[1,2‐a]indole derivative in calf thymus DNA (ctDNA) using various spectroscopy and computational techniques. The UV‐Vis absorption result shows that the binding interaction of pyrazino[1,2‐a]indole derivative in ctDNA complex may be in the non –covalent form and the binding associate constant Ka value was estimated 7.06×103 L mol−1 at 297 K. The fluorescence emission spectroscopy analysis suggested that pyrazino[1,2‐a]indole derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…From the plot, the binding constant K a = 4.75 × 10 6 L mol −1 is calculated and the number of binding sites for ctDNA n = 1.03. From the result, it is clear that the protein binds to DNA 17 . It can also be observed that the binding is class one that is, the protein has one possible site for the ctDNA to bind.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…From the plot, the binding constant K a = 4.75 × 10 6 L mol −1 is calculated and the number of binding sites for ctDNA n = 1.03. From the result, it is clear that the protein binds to DNA 17 . It can also be observed that the binding is class one that is, the protein has one possible site for the ctDNA to bind.…”
Section: Resultsmentioning
confidence: 86%
“…From the result, it is clear that the protein binds to DNA. 17 It can also be observed that the binding is class one that is, the protein has one possible site for the ctDNA to bind.…”
Section: Binding Constant and The Number Of Binding Sitesmentioning
confidence: 99%
“…3 The synthesis of annulated indoles attracts much attention too, e.g., pyrazino[1,2-a]indoles 4 are sought for heterocycles with a diverse array of biological activities. 5 Some representative examples, most relevant to current research, display antiproliferative activity, 6 bind to DNA, 7 and inhibit CK2, PIM1, and PIM2 8,9 (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%